2013
DOI: 10.1111/imb.12011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative metatranscriptomic signatures of wood and paper feeding in the gut of the termite Reticulitermes flavipes (Isoptera: Rhinotermitidae)

Abstract: Termites are highly eusocial insects that thrive on recalcitrant materials like wood and soil and thus play important roles in global carbon recycling and also in damaging wooden structures. Termites, such as Reticulitermes flavipes (Rhinotermitidae), owe their success to their ability to extract nutrients from lignocellulose (a major component of wood) with the help of gut-dwelling symbionts. With the aim to gain new insights into this enzymatic process we provided R. flavipes with a complex lignocellulose (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 77 publications
8
87
1
Order By: Relevance
“…Moreover, the microbial community itself can create these microenvironments (67). Biochemical coordination of the symbiont community with their host to extract nutrition also likely influences symbiont diversification (68,69). The biology of the symbionts must also complement the biology and behavior of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the microbial community itself can create these microenvironments (67). Biochemical coordination of the symbiont community with their host to extract nutrition also likely influences symbiont diversification (68,69). The biology of the symbionts must also complement the biology and behavior of the host.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity and complexity of the termite gut microbiota have been evaluated using molecular technology techniques based on 16S rRNA (Warnecke et al, 2007;Berlanga et al, 2011;Mathew et al, 2012). Recent studies have indicated that different dietary habits shape the structure of microbiota in the termite gut (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). Dietary manipulation induces measurable differences among gut bacterial communities, and the recalcitrance of plant substrates may be the major cause of this variation in the diversity and richness of gut bacterial communities (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that different dietary habits shape the structure of microbiota in the termite gut (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). Dietary manipulation induces measurable differences among gut bacterial communities, and the recalcitrance of plant substrates may be the major cause of this variation in the diversity and richness of gut bacterial communities (Boucias et al, 2013;Huang et al, 2013;Raychoudhury et al, 2013). However, influences on the abundance and diversity of the intestinal microbial of termite fed with different substrates containing various lignin and cellulose or hemicellulose remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to secreting host-derived digestive enzymes, this lower termite harbors a diversity of eukaryotic (protist) and prokaryotic (bacteria) symbionts in its hindgut, which is analogous to a fermentation chamber (Watanabe and Tokuda, 2010;Brune, 2014). Comparison of metatranscriptome profiles for wood and paper (cellulose)-fed termites has shed much light on putative lignocellulose degrading enzymes and detoxification enzymes potentially involved in lignin and metabolite degradation (Raychoudhury et al, 2013). In addition, detoxification and antioxidant enzymes including phenoloxidases, laccases, esterase, cytochrome P450s, catalases, superoxide dismutases, and glutathione peroxidases (GPX) were previously found upregulated in termites fed on lignin phenolics (Tartar et al, 2009;Coy et al, 2010;Sethi et al, 2013).…”
mentioning
confidence: 99%